The research was conducted on four wood species with small of diameter, originated from Sukabumi, i.e. huru gading (Litsea odorifera Val.), sampora (Colona javanica Burr.), kisampang (Evodia aromatica BL.) and nyatuh (Pouteria duclitan Bachni). The resistance properties of those four wood species after being metal-screwed against seven wood-destroying fungi were evaluated using modified DIN 52176 standard (Martawijaya, 1975). Results showed that decaying rates (weight losses) of the screwed wood - DJARWANTO .; Sihati SUPRAPTI (Jurnal Ilmu dan Teknologi Hasil Hutan, 2008)
The research was conducted on four wood species with small of diameter, originated from Sukabumi, i.e. huru gading (Litsea odorifera Val.), sampora (Colona javanica Burr.), kisampang (Evodia aromatica BL.) and nyatuh (Pouteria duclitan Bachni). The resistance properties of those four wood species after being metal-screwed against seven wood-destroying fungi were evaluated using modified DIN 52176 standard (Martawijaya, 1975). Results showed that decaying rates (weight losses) of the screwed wood were generaly greater than those of control (unscrewed wood). The highest weight loss was encountered on unscrewed kisampang wood exposed to Pycnoporus sanguineus HHB-324 (49.33%), while the lowest loss was found on unscrewed huru gading wood exposed to Dacryopinax spathularia (0.69%). Three of four wood species tested (i.e. sampora, kisampang and nyatuh) both being screwed and unscrewed were categorized as not resistant (class IV), whereas screwed huru gading wood was moderately resistant (class III) and the unscrewed one was resistant (class II). Based on corrosion, the highest weight loss of screw was obtained on kisampang wood tested by C. globosum (11.33%). However, the lowest screw weight loss was on huru gading tested by Polyporus sp. (1.95%). Among the fungi, the most severe attacks on wood was performed by P. sanguineus HHB-324. Based on ability to corrode wood-associated screw, there were no significant different among five of the seven fungi, whereas Polyporus sp. and  P. sanguineus HHB-324 were performed lower ability.   Keywords:  Resistance properties, wood destroying fungi, metal screw, weight loss